Grass Carp Mex3A Promotes Ubiquitination and Degradation of RIG-I to Inhibit Innate Immune Response - Jiang, Zeyin; Sun, Zhichao; Hu, Jihuan; Li, Dongming; Xu, Xiaowen; Li, Meifeng; Feng, Zhiqing; Zeng, Shanshan; Mao, Huiling; Hu, Chengyu (Frontiers in Immunology, 2022)
As one of the Mex3 family members, Mex3A is crucial in cell proliferation, migration, and apoptosis in mammals. In this study, a novel gene homologous to mammalian Mex3A (named CiMex3A, MW368974) was cloned and identified in grass carp, which is 1,521 bp in length encoding a putative polypeptide of 506 amino acids. In CIK cells, CiMex3A is upregulated after stimulation with LPS, Z-DNA, and especially with intracellular poly(I:C). CiMex3A overexpression reduces the expressions of IFN1, ISG15, and pro-inflammatory factors IL8 and TNFα; likewise, Mex3A inhibits IRF3 phosphorylation upon treatment with poly(I:C). A screening test to identify potential targets suggested that CiMex3A interacts with RIG-I exclusively. Co-localization analysis showed that Mex3A and RIG-I are simultaneously located in the endoplasmic reticulum, while they rarely appear in the endosome, mitochondria, or lysosome after exposure to poly(I:C). However, RIG-I is mainly located in the early endosome and then transferred to the late endosome following stimulation with poly(I:C). Moreover, we investigated the molecular mechanism underlying CiMex3A-mediated suppression of RIG-I ubiquitination. The results demonstrated that Mex3A truncation mutant (deletion in the RING domain) can still interact physically with RIG-I, but fail to degrade it, suggesting that Mex3A also acts as a RING-type E3 ubiquitin ligase. Taken together, this study showed that grass carp Mex3A can interact with RIG-I in the endoplasmic reticulum following poly(I:C) stimulation, and then Mex3A facilitates the ubiquitination and degradation of RIG-I to inhibit IRF3-mediated innate antiviral immune response.